Uberland: a cartografia artística sobre o imaginário social urbano da cidade de Uberlândia-MG/Brasil - Silva, Richard Augusto da (2019)
Submerged in the memory, in this research the history of the city of Uberlândia/MG was investigated trodden in three paths the history. Both the theoretical approach, a web memorial is produced composed by symbols, images, and illustrations, figurative in the measure in that the facts and contexts are revealed spill of the progress, imaginary place that acts on the urban social sphere of the city. Through an anthropological glance on the study of the imaginary, the web memorial and the imaginary of the progress were analyzed in synthesis with the anthropological itinerary of the imaginary. In that scenery, the symbols and images were systematized selected in the web memorial, reordaining them in the process of poetic production of the artistic cartography "Uber Land: the island garden of the Interior of the Rotten Flour." As artistic device, the cartography was projected in a virtual platform, elaborated by programming language, animation effects and interaction, in crossing with the memory of Uberlândia and the imaginary of the progress.